Risk parity diversification - Tsolo, Leemisa Neo (My University, 2019)
The South African Listed property sector has been in existence for over twenty years, and on 1st April 2013 Section 25BB of the Income Tax law allowed property companies to convert into Real Estate Investment Trusts (REITs). The 2008 Global Financial Crises (GFC) revealed flawes in traditional portfolio allocation strategies, and the subsequesnt periods revealed how correlated assets were, and especially property assets. This study proposes an alternative portfolio construction paradigm borrowed from finance namely, the concept of Risk Parity (RP). RP portfolios derive their logic from portfolio diversification which originates from the Modern Portfolio Theory (MPT). This study employs a vector autoregressive (VAR) model as an asset selection tool, and proposes a RP portfolio as a better risk adjusted portfolio, which will be suitable to be a core portfolio strategy. Limitations of the proposed Risk Parity strategy is that it has not found its place in main stream financial product offerings on the market, partly due to the extant literature on the subject, though it is based on a more quantifiable risk as a guiding principle. The VAR model is ideally usable in the medium. Findings were that Listed companies in South Africa still allocate their investments in the traditional property assets and they either diversify geographically and sectorally. The paper proposes that investors consider the implictions of the business cycle stages when making real estate allocations, and even further when investorsconsider listed real estate, the exploration of more robust models such as the RP strategy will reduce the potential losses that were seen in the aftermath of the 2008 GFC